Anatomical Study of the Epidermal Leaves, Stems and Corall of Genera SecurigeraDC., SophoraL. and TavernieraDC. (Leguminosae) in Iraq - A.A., Susa; Z.Q.A., Al-Kulaby (Al-Qadisiyah Journal of Pure Science, 2018)
The current research was conducted anatomical study of the epidermal leaves and stems and Corall for kind genera species of family (Leguminosae),and these genera are SecurigeraDC. , SophoraL. and TavernieraDC. in Iraq,which included one species (S .securidaca) of the first genus and two species(So .gibbosaÙˆSo .japonica) of second genus, and one species(T.nummularia) for third genus. Studied the anatomical characteristics to epidermal of leaves, stemsand corall to species of genera under study, included ordinary epidermal cells and stomatal complex to leaves and stems as well as Indumentum among these genus , gives shape of Anticlinal cell walls of epidermal taxonomic value important qualities in diagnosis and isolate characteristics Undulate which has it species S .securidaca was special other species for genus SophoraL. other species and stomata was find and lose in epidermal stem important in isolate and diagnosis also characteristics striation in cuticle and occurrence of crystals and absence good characteristics for taxonomy of the species in this study. Botany Classification: QK 640-(707)